The Idea of Emancipatory Education in the Proposals of Students of Early Childhood Education - Barbara Dudel (Maria Curie-Skłodowska University, Lublin, Poland, 2018)
The main aim of this article is to present the analysis of the approaches to the idea of emancipation in grades 1-3. The study was conducted by the second-year students of the second degree of pedagogy of early childhood. This article attempts to identify the values recognized by the authors of works to be important in early childhood education, preferred ways of achieving the goals and the teacher-student relationship. The results of analysis of educational projects enrich the research participants' statements. The last part of the text are the conclusions.